Influencing Mechanism of Guizhou Consumer Satisfaction on Rural E-Commerce Logistic Model in Agricultural Products - Tangzhi Pan (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
The rapid advancement of technology has fundamentally transformed our daily lives, particularly in the internet and databases. In the agricultural sector, integrating e-commerce platforms in rural areas has ushered in a new era of opportunity for farmers and producers. By leveraging efficient logistics systems, these platforms have enabled them to tap into broader markets. Furthermore, they have proven instrumental in enhancing rural farmers' growth, efficiency, and market access. As rural areas undergo revitalization, e-commerce platforms play a pivotal role in the development of agriculture. Their impact is far-reaching, fostering diversification, adopting intelligent agricultural practices, and establishing e-commerce trading and delivery platforms. The number of respondents for this study was 390, with its focus on the intricacies of the e-commerce development strategy for consumer satisfaction in rural areas is of utmost importance. It aims to spotlight the logistics model and specific development strategies that will further the advancement of e-commerce in rural regions, all within the broader context of rural revitalization.